“BROMANCE” HOMOSOCIAL RELATIONSHIPS (Telaah Filosofis Kritis terhadap pola relasi sesama lelaki dalam kehidupan sosial) - Richardo Gerry Heru Cornelis; Juandi Juandi (Aggiornamento, 2021)
The focus of this paper is a term that is often discussed today, namely "bromance". This bromance phenomenon is often found in the social reality of this modern age, but sometimes the understanding and conception of the word bromance is not understood and even misguided and immediately considers this relationship very unnatural to be shown socially. It is undeniable that bromance relationships are often associated with relationships between men who are physically bound, as well as sex and psychological relationships. The concept of friendship in this modern era has become one of the reasons why the concept of bromance can rampant, they even dare to deliberately appear in the reality of everyday life. Starting from this, this paper wants to clarify the meaning of the word "bromance" along with the characteristics of relationships and examples, as well as constructing the boundaries of the difference between homosexuals and bromance. The methodology used is a library study by taking sources from several books and related articles.